Toxoplasmosis: An overlooked cause of confusion in a patient with myasthenia gravis. (October 2020) - Lee, Marco; Sethi, Kavita; Guy, Edward
Abstract: Background: Immunosuppressive medications are often under-recognised risk factors for toxoplasmosis in non-HIV persons. Case report: A 58-year-old male presented to our hospital with a three-day history of confusion, change in behaviour, and vomiting. Diffusion-weighted MRI revealed two frontal and one thalamic ring-enhancing lesions associated with significant oedema, suspicious of multiple cerebral abscesses. The patient underwent surgical brain biopsies twice to establish the pathological diagnosis. After negative bacterial and fungal cultures and 16S rDNA PCR results, a suspicion of cerebral toxoplasmosis was made after noting exposure to mycophenolate mofetil (MMF) as an immunosuppressive agent for myasthenia gravis. Result: The diagnosis was suggested by positive toxoplasma serum IgG, Sabin-Feldman dye test, and brain tissue PCR. Following anti-toxoplasma treatment and cessation of MMF, the patient made a good neurological and functional recovery. Conclusion: This is the first described case of cerebral toxoplasmosis developing on MMF monotherapy, with six other published cases developing on MMF with other concurrent immunosuppressant medication. These few descriptions suggest a rare or under-reported phenomenon. This case highlights the importance of considering cerebral toxoplasmosis in non-HIV persons on immunosuppressive therapy for inflammatory neuromuscular disorders. Highlights: Immunosuppressive medications are often under-recognised risk factors for toxoplasmosis in non-HIV persons. This is the first described case of cerebral toxoplasmosis developing on MMF monotherapy, with six other published cases developing on MMF with other concurrent immunosuppressant medication. This case highlights the importance of considering cerebral toxoplasmosis in non-HIV persons on immunosuppressive therapy for inflammatory neuromuscular disorders.